2018
DOI: 10.1016/j.canep.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Risk of high-grade serous ovarian cancer associated with pelvic inflammatory disease, parity and breast cancer

Abstract: Our finding of an increased risk of HGSC associated with PID lends support to the hypothesis that inflammatory processes may be involved in the etiology of HGSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
(98 reference statements)
2
14
0
Order By: Relevance
“…Consequently, underdiagnosis of any abdominal compliant may lead to life-threatening situations such as overgrowth or torsion of ovarian masses [32] . About 70% of the patients had no parity which confirms the other studies that have been claimed low parity is related to ovarian cancer [33] . From about 30% who had childbirth, the highest percentage was related to a child with 55%.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, underdiagnosis of any abdominal compliant may lead to life-threatening situations such as overgrowth or torsion of ovarian masses [32] . About 70% of the patients had no parity which confirms the other studies that have been claimed low parity is related to ovarian cancer [33] . From about 30% who had childbirth, the highest percentage was related to a child with 55%.…”
Section: Discussionsupporting
confidence: 86%
“…Given the likely extra-ovarian origin of a proportion of EOCs, exposures associated with tubal pathologies are of increasing interest with respect to EOC risk. Sexually transmitted infections (STIs) are associated with a range of gynecologic sequelae including pelvic inflammatory disease (PID), 6,7 PID has been associated with EOC risk, 8,9 though data to date suggest strongest associations with borderline tumors. 10 Chlamydia trachomatis and Mycoplasma genitalium are two sexually transmitted bacterial causes of PID.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to C. trachomatis and chsp60 is associated with pelvic inflammatory disease (PID) [19,20]. Recent studies have shown an increased risk of HGSC after PID [21,22]. During an inflammatory process, the glycoprotein mucin 1 (MUC1), normally expressed by epithelial cells, are overexpressed to provide a barrier between the epithelium and the extra cellular milieu against infections [23].…”
Section: Introductionmentioning
confidence: 99%